Cohesion properties and fracture toughness of Fe/W interfaces with additions of Re and Cr. (January 2022) - Wang, Qian; Chen, Nan; Du, Guoping; Jiang, Changshuang; Chen, Liang
Abstract: First-principles calculation has been used to comparatively investigate that the stability of Re and Cr at the Fe/W interface, as well as cohesion characteristics and fracture toughness. It is found that Re atom prefers to situate at the Fe position at the interface layer, and the reason is due to the surrounding W–Re and Fe–Re bond lengths are much shorter than other substitution positions of Fe/W interface. Our calculations also reveal that the different effects of the additions of Re and Cr on the cohesion properties and fracture toughness of Fe/W interface, i.e., substituting Re for interfacial Fe position could increase cohesion strength and fracture toughness, which appeared the volatile changes by the Cr substitutions for Fe. The derived results are deeply understood by means of electronic structures, and sufficiently compare with experimental observations in the literature. Highlights: Substitution of Fe by Re in Fe/W interface layer is energetically favorable. Cr atom in Fe lattice migrates preferentially into Fe/W interfaces. Substituting Re for Fe position increases the cohesion strength and fracture toughness of Fe/W interface. Re and Cr have different effects on cohesion properties and fracture toughness of W/Fe interfaces.